Analysis of resistance to stem rust and identification of Sr genes in introgressive lines of spring bread wheat - O. A. Baranova; S. N. Sibikeev; E. A. Konkova (Труды по прикладной ботанике, генетике и селекции, 2023)
Background. Due to the increase in the harmfulness of wheat stem rust (Puccinia graminis f. sp. tritici Erikss. & E. Henn.) in the Volga region, and the likelihood of the spread of the aggressive Ug99 race, an assessment of the genetic diversity of wheat breeding lines and identification of effective Sr genes are of fundamental importance.Materials and methods. Ninety spring bread wheat introgressive lines with stem rust resistance, developed at the Federal Center of Agriculture Research of the South-East Region, were analyzed. Molecular markers were used to identify resistance genes: Sr24/Lr24, Sr25/Lr19, Sr26, Sr28, Sr31/Lr26, Sr32, Sr36, Sr38/Lr37, Sr39 and Sr57/Lr34. The analysis of plants for resistance was carried out according to standard methods; the Stakman scale was applied to determine the type of reaction.Results. The genes Sr31/Lr26, Sr25/Lr19, Sr57/Lr34, Sr38/Lr37 and Sr39/Lr35 were identified in the analyzed breeding lines. Sr25 was found in 51 lines (56,7% of samples), Sr31 in 41 lines (45.6%), Sr57/Lr34 in 5 lines, Sr38 in 10 lines and Sr39 in one line. Combinations of resistance genes were identified: Sr31+Sr25 in 28 lines (31.1%), Sr25+Sr38 in 5 lines, and Sr25+Sr39 in one line. The Sr24/Lr24, Sr26, Sr28, Sr32 and Sr36 genes were not identified.Conclusion. As a result, promising highly resistant introgressive wheat lines with promising combinations of Sr31+Sr25, Sr25+Sr38 and Sr25+Sr39 genes were identified. They can be used in Russian breeding programs for immunity.